Characteristics of Procalcitonin Values and Absolute Neutrophil-Lymphocyte Ratio in Pneumonia Sepsis Patients in the Intensive Care Unit of a Hospital H. Adam Malik - Angela Yurika Purba; Syamsul Bihar; Bintang YM Sinaga (CV. Inara, 2026)
.Sepsis pneumonia ranks among leading causes of global mortality, particularly in ICU settings, yet local biomarker profiles remain underexplored in resource-limited contexts like Indonesia. This study aimed to characterize procalcitonin (PCT) and absolute neutrophil-lymphocyte ratio (NLR) in ICU sepsis pneumonia patients at RSUP H. Adam Malik Medan (2023). Employing an observational analytic cross-sectional design, total sampling captured 132 patients meeting Sepsis-3 criteria (qSOFA ≥2, SOFA ≥2, age ≥18 years) with complete PCT/NLR data. Secondary data from medical records were analyzed using SPSS 25 via univariate descriptives and Spearman bivariate tests. Results revealed demographic dominance of males (61.37%) and age ≥60 years (40.15%), lymphopenia (94.70%), neutrophilia (90.90%), critical NLR (>17; 50%), and PCT predominantly in sepsis/infection range (0.5-2 ng/mL; 39.39%) followed by septic shock (>10 ng/mL; 29.55%). In conclusion, elevated NLR and PCT confirm severe inflammation patterns aligned with Sepsis-3, supporting biomarker-guided therapy to mitigate antibiotic overuse in Indonesian ICUs.